Impact of cinema on tourism: the case of Brazil - Cabañas, Rodrigo Tovar; Villanueva Hernández, Hipólito; Escobedo, José Vicente Jaramillo (Anais Brasileiros de Estudos Turísticos, 2023)
The importance of this work lies in the fact that more and more, the tourism sector is shaping up to reach double digits in its participation in the world gross domestic product, coupled with the fact that, in countries such as Brazil, its productive linkages affect the spatial dynamics of the localities. Therefore, this article goal to develop a cartogram of the places filmed in Brazil, to document the filmic strengths of each federative entity of the Brazilian Republic and thus contribute elements to characterize the course that the different agendas could follow. Federation tourism. It should be noted that the methodological treatment is an effort to approach the Big Data phenomenon, the search was carried out through four million film titles. Among the most pressing results, depending on the cinematographic genre, the leading site around Brazilian film locations varies, for example, if the genre is science fiction, the case of Salvador de Bahía stands out, instead if the genre is documentary highlights the state of Pará.